Effect of Tryptophan Dietary Content on Meagre, Argyrosomus regius, Juveniles Stress and Behavioral Response - Vasconcelos, Ana (2023)
Funding Information: This study was supported by the project AQUARAS (MAR-02.01.02-FEAMP-0223). M.C.S. is supported by the Foundation for Science and Technology through an individual contract (2021.01458.CEECIND). Publisher Copyright: © 2023 by the authors.